Identifying Problems and Prospects of Media Professionals Working in Khyber Pakhtunkhwa: A Case Study of Peshawar Based Journalists - Rauf, Abdur; Riaz, Saqib; Safdar, Ghulam (Journal of Peace, Development and Communication, 2021)
The study conducted to find out problems related to journalist’s career as well as to search out the media professionals view point regarding journalists’ problems in Peshawar. Data collected from the Peshawar press club journalists comprises 363 members. It is found that 86% of the respondents consider permanent job category is related to good performance while 89% of the respondents termed job insecurity do affect journalists’ professional performance. The chi-square results showed that proportion of male views is not significantly different from female regarding the job performance. Both of the genders believe that if the job will secure the performance would be fruitful. The results specified no significant association between status and job security because a significant proportion of married views is significantly different from unmarried regarding the job security. The Chi-square test for independence showed there is no significant association between status and administrative rules. Study concluded that media professionals are facing problems due to job security, administrative and financial problems.